Internet Financial Reporting in Syria An Exploratory Study - Issa, Reem (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aims to investigate the presence of websites for the registered companies in the Syrian Commission of Financial Markets and Securities (SCFMS). It also identifies the level of the Internet Financial Reporting (IFR) of the companies that have presence on the world wide web; and the information they use to report on their websites. The study is applied on 46 registered companies within the first quarter of 2017. The websites' presence of the registered companies are investigated by the Companies' Information link on the SCFMS webpage. Google search engine is used to find the websites of some companies that were not available on SCFMS webpage. A checklist is developed using the scoring system to measure IFR level. The findings show that 54% of the registered companies have reachable websites. They also show that the level of IFR in Syria is still in its infancy. The registered companies seem to be interested in the financial items of reporting more than the other items. التقرير المالي على الانترنت في سورية دراسة استكشافية هدفت هذه الدراسة إلى التحقق من وجود مواقع الكترونية للشركات المسجلة في هيئة الأوراق والأسواق المالية السورية، بالإضافة إلى تحديد مستوى التقرير المالي على الانترنت للشركات التي تملك مواقع الكترونية، وتحديد المعلومات التي تقوم بالتقرير عنها عبر مواقعها الالكترونية. أجريت الدراسة على 46 شركة مسجلة في الهيئة خلال الربع الأول من عام 2017. تم التحقق من وجود مواقع الكترونية للشركات المسجلة في الهيئة، عبر رابط معلومات الشركات ضمن صفحة هيئة الأوراق والأسواق المالية السورية، كما تم الاستعانة بمحرك بحث Google للوصول إلى عناوين المواقع الالكترونية لبعض الشركات التي لم تنشر عنوان موقعها الالكتروني على صفحة الهيئة. هذا وقد تم تطوير قائمة تعتمد على نظام النقاط لقياس مستوى التقرير المالي على الانترنت. أظهرت النتائج أن 54 % من الشركات المسجلة في هيئة الأوراق والأسواق المالية السورية تملك مواقع الكترونية على الانترنت يمكن الوصول إليها، كما بينت أن مستوى التقرير المالي على الانترنت في سورية مازال متدنياً. أظهرت الشركات اهتماماً بالتقرير عن العناصر المالية بنسبة أكبر من اهتمامها بالتقرير عن بقية العناصر.